Jukujikun Learning to Improve Kanji Reading Skills - Fanani, Urip Zaenal; Mintarsih, Mintarsih; Parastuti, Parastuti; Sopaheluwakan, Yovinza Bethvine; Suryawati, Cicilia Tantri (Proceeding of International Joint Conference on UNESA, 2025)
When learning Japanese, one cannot be separated from Kanji, as it is one of the essential writing systems used in the language. Kanji is particularly interesting because one might assume that if a person can write a character, they can surely read what they have written. However, this assumption does not hold true for Kanji. Even if someone can write a Kanji character, it does not necessarily mean they can read it. This challenge arises due to the existence of Jukujikun, which are specific readings that do not follow standard pronunciation rules. The difficulty in learning Jukujikun readings is experienced not only by learners but also by lecturers, as they may be unfamiliar with these non-standard readings of two-character Kanji compounds. To reduce the difficulties Indonesian learners face in mastering Jukujikun readings, the material is repeated several times until learners feel that the challenges of the Jukujikun readings have been successfully overcome.